Analysis of The Effect of Product Price, Product Image and Customer Satisfaction as a Mediation on Brand Loyality of Canned Fish Product from ABC Brands - Agan Sasongko Aji; Nuddin Harahab (Faculty of Fisheries and Marine Science, Brawijaya University, 2018)
This research aims to analyze the influence of product price, product image and customer satisfaction as a mediation variable to brand loyality of ABC brand canned product. The research method used is descriptive with qualitative and quantitative data analysis using analysis of Structural Equation Modeling (SEM) based on Partial Least Square (PLS). Methods of data collection using questionnaires with data collection convenience sampling technique. The results showed that product image and customer satisfaction directly affect the brand loyality. While the product price variable directly or indirectly not significant